2013
DOI: 10.1186/1472-6947-13-11
|View full text |Cite
|
Sign up to set email alerts
|

Towards plug-and-play integration of archetypes into legacy electronic health record systems: the ArchiMed experience

Abstract: BackgroundThe dual model approach represents a promising solution for achieving semantically interoperable standardized electronic health record (EHR) exchange. Its acceptance, however, will depend on the effort required for integrating archetypes into legacy EHR systems.MethodsWe propose a corresponding approach that: (a) automatically generates entry forms in legacy EHR systems from archetypes; and (b) allows the immediate export of EHR documents that are recorded via the generated forms and stored in the EH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Although interactivity is generally sought by people experiencing schizophrenia spectrum disorders or other psychotic disorders, sites devoted to schizophrenia and psychoses offer limited interactivity when compared to other information sites [71]. …”
Section: Resultsmentioning
confidence: 99%
“…Although interactivity is generally sought by people experiencing schizophrenia spectrum disorders or other psychotic disorders, sites devoted to schizophrenia and psychoses offer limited interactivity when compared to other information sites [71]. …”
Section: Resultsmentioning
confidence: 99%
“…Consistently, in a previous analysis to understand trade-offs African Americans and Whites employ in making cancer pain decisions, we found that African Americans were more likely to make analgesic use decisions based on side-effects whereas Whites were more likely to make analgesic use decisions based on amount of relief expected from using pain medications. 24 …”
Section: Discussionmentioning
confidence: 99%
“…This approach enables the development of specific transformationss that produce the artefacts needed for a certain use case. Similar approaches for generating entry forms based on openEHR CIMs were presented by Atalag [25], Chen [32] and Duftschmid [33].
Fig.
…”
Section: Resultsmentioning
confidence: 94%